White halo around a congenital melanocytic naevus - Nayak, Vijayalakshmi; Nakka, Monica (International Journal of Research in Dermatology, 2022)
This is a case report of Sutton nevus/ Halo naevus/ leukoderma acquisitum centrifugum in a young boy around congenital melanocytic naevus without any associated vitiligo. Halo naevi occur in 1% of the white population. The prevalence is higher in patients with Turner syndrome. It can occur at any age but frequently occurs in a young person. It can be associated with vitiligo and turner syndrome. Postulated pathogenesis is destruction of the melanocytes by cytotoxic T cells. There is frequently lymphocytic infiltration around the naevus in the histopathological examination, and ultrastructurally we can see cytotoxic changes in the naevus cells. It is mainly seen around the acquired congenital naevus but can also occur around spitz naevi, neurofibroma, primary or secondary malignant melanoma. 50% Sutton naevus regress in months to years. Usually, no treatment is required unless, when in doubt, you can do an excision biopsy. Our patient was managed conservatively and followed every six months. This case is being reported because of the condition’s rarity and for learning purposes.